Thinking about and enacting curriculum in "frames of war" - Naqvi, Raht.; Smits, Hans.; ebrary, Inc. (Lanham : Lexington Books, 2012)
"Rahat Naqvi and Hans Smits' edited collection, "Thinking about and Enacting Curriculum in 'Frames of War'" is centered on the theme of how the current global order creates precarious conditions for human life. The contributors respond to the challenges Judith Butler posed about the fragility of life and questions about how we apprehend, and take up ethically, our responsibilities for those who are considered "Other." The overarching objective of the book is the meaning of a call to ethics, and how discussion of framing and frames is a provocation to think about our responsibilities as curriculum scholars and practitioners"-- Provided by publisher.
Machine generated contents note: Table of Contents -- About the Cover -- Acknowledgments -- Introduction: The World on the Verge of a Nervous Breakdown, by Rahat Naqvi & Hans Smits -- Chapter One: Challenging the Frames of Curriculum Hans Smits & Rahat Naqvi -- Chapter Two: Facing the War in Afghanistan: A Curriculum Journey of a "Good Canadian", by David Blades -- Chapter Three: Re-Framing: Un-Neighbourly Love, Haunting Inquiry, Perfectibility, by Robert Nellis -- Chapter Four: Sound Curriculum: Recognizing the Field, by Walter Gershon -- Chapter Five: Running head: After the war Narrative Reconstructions, Broken Frames: Sendai Before and After the War, by Craig McDonald -- Chapter Six: Depicting and Framing the Trauma of Another, by Patricia Kostouros -- Chapter Seven: Teaching Social Justice in English Language Arts: Working Toward Transformative Learning, Karen Magro -- Chapter Eight: Global Justice Education as a Pedagogy of Loss: Interrupting Frames of War, by Lisa Taylor -- About the Authors -- Bibliography -- Index -- Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Curriculum planning -- Philosophy; Critical pedagogy; Education -- Aims and objectives; War and education; Electronic books